Institutional change in German vocational training: from collectivism to segmentalism - Thelen, Kathleen [Verfasser]; Busemeyer, Marius R. [Verfasser] (My University, 2012)
"Dieses Papier dokumentiert den graduellen, aber transformativen Wandel des deutschen Berufsbildungssystems von einem kollektivistischen zu einem stärker segmentalistischen Modell. Zunächst wird gezeigt, dass die beiden Logiken des Kollektivismus und des Segmentalismus in der Geschichte der beruflichen Bildung schon immer in einem Spannungsverhältnis standen. Im empirischen Teil wird gezeigt, dass die segmentalistische Dimension während der letzen drei Jahrzehnte gegenüber der kollektivistischen an Bedeutung gewonnen hat. Dies wird anhand der Entwicklung der Ausbildungsbeteiligung von Unternehmen sowie der Politik der beruflichen Bildung dokumentiert. Insbesondere werden drei Fallstudien zur Debatte über Modularisierung und Europäisierung der beruflichen Bildung, zur (Wieder-)Einführung zweijähriger Ausbildungsberufe und zum sich anbahnenden Konflikt über die Organisation von Prüfungen präsentiert. Abschließend werden Parallelen zwischen dem Wandel der beruflichen Bildung und den Arbeitsbeziehungen im Allgemeinen herausgearbeitet." (Abstract des Discussion Paper)

This contribution tries to underpin the hypothesis of a noticeable shift of the German vocational training system from a strongly "collective" orientation, which is organized around the production of broad and portable occuptational skills, towards a less encompassing, more "segmentalist" training system based on increasingly differentiated skills more closely aligned to the internal needs of large companies engaged in training. It developes the argument in three steps. First it discusses the two logics of collectivism and segmentalism, and how the German system is characterized by longstanding tensions between competing collectivist and segmentalist interests. The main historical developments of the collective skill system in Germany were (1) the instutionalization of skill certification (1890s-1900s), the advance of skill standardization (1920s-1930s), and (3) the deepening and boradinening of occupational skill profiles (1970s-1980s). The following section deals with "observable recent trends, tracking the effects they have had on each of the dimensions (certification, standardization, deepening, and broadening) to document and to explain the re-emergence of segmentalist tendencies." It is argued that the centralization of collective bargaining has been crucial to the maintenance of a collective training system. On the other hand it is shown how increasing flexibilization of bargaining (through decentralization and declining collective bargaining coverage) has been accompanied by heightened pressure for a flexibilization of training as well. "The analysis relies on primary sources as well as insights from more than twenty-five semi-structured interviews, conducted between 2006 and 2008, with stakeholders and representatives from unions (UN), employers (EMP), and the state bureaucracy (ST). A final section contemplates the implications of these developments in the context of emerging strong tendencies toward dualism in the German labor market." (Textauszug, BIBB-Doku)
Vorab erschienen als "MPIfG Discussion Paper 08/13", http://www.mpifg.de/pu/mpifg_dp/dp08-13.pdf [Zugriff 1.6.2012]
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 2.1.6 Arbeits- & Tarifrecht; S 2.2.1 Ordnung von Ausbildungsberufen; Berufsbildungssystem; Berufsbildungspolitik; Historische Entwicklung; Ausbildungsbeteiligung; Tarifvertrag; Neuordnung der Ausbildungsberufe; Zweijähriger Ausbildungsberuf; Flexibilisierung; Reform